2013
DOI: 10.1002/clc.22173
|View full text |Cite
|
Sign up to set email alerts
|

Oral Anticoagulants to Reduce the Risk of Stroke in Atrial Fibrillation: How Should a Clinician Choose?

Abstract: Atrial fibrillation (AF), a common arrhythmia that occurs with increasing frequency in the aging population, is associated with increased mortality and morbidity. To ensure that patients receive adequate anticoagulant prophylaxis, clinical guidelines for anticoagulation advocate use of validated scoring systems to stratify patients by cardiovascular risk and predict the individual patient's risk of adverse effects of therapy. Recently approved oral anticoagulants-a direct thrombin inhibitor and the factor Xa i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Rivaroxaban (Xarelto®) and apixaban (Elequis®) reach peak plasma concentration at around 3 hours and are well tolerated, exhibiting fewer side-effects than dabigatran. 42,43 Owing to the mechanisms of elimination, both drugs should be avoided in hepatic failure but can be used in mild to moderate renal failure. 44,45 Apixaban can be used safely at a reduced dose in severe renal failure.…”
Section: Direct Factor Xa Inhibitors: Rivaroxaban and Apixabanmentioning
confidence: 99%
See 3 more Smart Citations
“…Rivaroxaban (Xarelto®) and apixaban (Elequis®) reach peak plasma concentration at around 3 hours and are well tolerated, exhibiting fewer side-effects than dabigatran. 42,43 Owing to the mechanisms of elimination, both drugs should be avoided in hepatic failure but can be used in mild to moderate renal failure. 44,45 Apixaban can be used safely at a reduced dose in severe renal failure.…”
Section: Direct Factor Xa Inhibitors: Rivaroxaban and Apixabanmentioning
confidence: 99%
“…48,49 Early trials demonstrated that rivaroxaban and apixaban were as effective as warfarin in the management of non-valvular AF with fewer bleeding complications. 43,50 Both drugs have also been shown to be as effective as LMWH in the prophylaxis of venous thromboembolism (VTE) in orthopaedic surgery patients and, again, fewer bleeding issues were observed. 42, 51,52 Enoxaban is another direct Xa inhibitor which may show promise in the future but has not yet been fully researched or approved for use.…”
Section: Direct Factor Xa Inhibitors: Rivaroxaban and Apixabanmentioning
confidence: 99%
See 2 more Smart Citations